Analisis Penambahan Limbah Karbit Sebagai Substitusi Semen Terhadap Kuat Tekan Mortar - Pratama, Eza Dafa; Rochmah, Nurul; Firmansyah, Mochammad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Cement, as one of the ingredients in making mortar, has a significant impact on the environment. As an alternative to the use of cement, carbide waste can be used as a substitute for cement. Carbide waste is a by-product of the welding industry in the form of a grayish solid. One of the contents of carbide waste is CaO, CaO itself is one of the contents of cement. The CaO element has potential in making mortar and can increase compressive strength. This study aims to analyze the impact of adding carbide waste as a partial substitute for cement to the mortar mixture. In this study, the percentage of carbide waste addition as a cement substitute was 0%, 2.5%, 5%, 7.5%, and 10%. This study aims to determine the optimum percentage of the mortar mixture with the addition of carbide waste. The research method used includes laboratory testing of the mortar mixture with varying levels of carbide waste to analyze the compressive strength. The results of this study concluded that the most optimum mortar compressive strength is at a percentage of 7.5% with a compressive strength of 29,430 MPa. However, at a percentage above 7.5% the compressive strength of the mortar decreased.